1992
DOI: 10.1159/000186739
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effect of Superoxide Dismutase on Adriamycin Nephropathy

Abstract: A single intravenous injection of adriamycin (ADR) results in marked proteinuria and glomerular morphological changes that are similar to minimal-change disease in humans. We examined the effect of superoxide dismutase (SOD) on ADR-induced proteinuria. ADR in a dose of 7.5 mg/kg body weight significantly increased urinary protein by day 14; proteinuria rapidly increased thereafter. Concurrent administration of SOD (50 mg/kg) over 30 min prior to and 30 min following ADR injection markedly reduced proteinuria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 9 publications
2
56
0
Order By: Relevance
“…In another study performed on Wistar rats, SOD activity has been significantly decreased in B(a)P treated group [25]. It has been also reported that 7.5 mg/kg doxorubicin induces superoxide dismutase [14]. In our study, SOD activity and MDA increased while CAT activity decreased following a long-term B(a)P treatment, and SOD activity slightly decreased in 4 mg/kg doxorubicin treated group.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In another study performed on Wistar rats, SOD activity has been significantly decreased in B(a)P treated group [25]. It has been also reported that 7.5 mg/kg doxorubicin induces superoxide dismutase [14]. In our study, SOD activity and MDA increased while CAT activity decreased following a long-term B(a)P treatment, and SOD activity slightly decreased in 4 mg/kg doxorubicin treated group.…”
Section: Discussionsupporting
confidence: 71%
“…Doxorubicin is bound to sugar-phosphate structure by cross-linking the DNA after penetrating into close base pairs of the DNA chain in rapidly reproducing cancerous cells. It damages the DNA structure and consequently the RNA synthesis [14,15]. Excretion of doxorubicin occurs predominantly by the hepatobiliary route and partially by the kidneys.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 It was also suggested that ADR-mediated ROS markedly increase the peroxidation of membrane polyunsaturated phospholipids and this lipid peroxidation level in vivo may be involved in the nephrotoxicity of ADR. 28 At the end of the treatment period of drug, we observed that the ADR treatment significantly reduced the MMP and slightly ATP level.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, adriamycin-, puromycin-, or cisplatin-induced nephrotic syndrome has been reported to be exacerbated by reactive oxygen species. [15][16][17][18][19][20] In addition, studies have reported that the antioxidant vitamin E and the antihypercholesterolemic agent probucol reduce nephrotoxicity. 21,22) However, few drugs with antioxidant activity are clinically available, and such drugs are not used for antioxidant purposes.…”
Section: Discussionmentioning
confidence: 99%